ANALISIS PEMEROLEHAN BAHASA ANAK YANG DIPENGARUHI OLEH FAKTOR LINGKUNGAN - Siti Syaidah Maysaroh (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2020)
Language is a form of sound symbol that is arranged regularly, by a number of components with rules that have meaning in each speech. If language has no meaning it will be more difficult to understand its meaning and purpose. So that with human language it will be easier to socialize. One of the development of children's abilities at an early age is language skills, even though the language speech is not yet perfect. This speech system will be more perfect as the child gets older. The purpose of this study is to analyze environmental factors that influence children's language development. This research uses storytelling method. The storytelling method is a way of conveying events, feelings, knowledge through improvised pictures, words, or sounds. The result of this research is that there is a mixture of language that is not synchronous when the child is invited to communicate. The loss of letters when pronouncing words and their pronunciation is not correct, because languages at this age are still in the development stage. Language is very important for all of us, especially in childhood it must be considered. Not paying attention will result in asynchronous language and word inaccuracies. The language taught by parents does not always have to use Indonesian, it needs to be familiarized with the language of the environment.